Highly crystalline polyimide covalent organic framework as dual-active-center cathode for high-performance lithium-ion batteries - Yao, Liyi (2023)
Polyimide covalent organic framework (PI-COF) materials that can realize intrinsic redox reactions by changing the charge state of their electroactive sites are considered as emerging electrode materials for rechargeable devices. However, the highly crystalline PI-COFs with hierarchical porosity are less reported due to the rapid reaction between monomers and the poor reversibility of the polyimidization reaction. Here, we developed a water-assistant synthetic strategy to adjust the reaction rate of polyimidization, and PI-COF (COFTPDA-PMDA) with kgm topology consisting of dual active centers of N,N,N',N'-tetrakis(4-aminophenyl)-1,4-benzenediamine (TPDA) and pyromellitic dianhydride (PMDA) ligands was successfully synthesized with high crystallinity and porosity. The COFTPDA-PMDA possesses hierarchical micro-/mesoporous channels with the largest surface area (2669 m2/g) in PI-COFs, which can promote the Li+ ions and bulky bis(trifluoromethanesulfonyl)imide (TFSI-) ions in organic electrolyte to sufficiently interact with the dual active sites on COF skeleton to increase the specific capacity of cathode materials. As a cathode material for lithium-ion batteries, COFTPDA-PMDA@50%CNT which integrated high surface area and dual active center of COFTPDA-PMDA with carbon nanotubes via π-π interactions gave a high initial charge capacity of 233 mAh/g (0.5 A/g) and maintains at 80 mAh/g even at a high current density of 5.0 A/g after 1800 cycles.